(untitled) (Semiárida, 2018)
Phomopsis helianthi is a fungus causing stem canker in sunflower plants. This disease occurs occasionally in Argentina, but the increase of sustainable agriculture practices might stimulate crop infection through plant debris left on the soil surface which becomes a niche for fungus propagules. Therefore, it is important to study the behaviour of sunflower hybrids exposed to attacks by this fungus. As the objective for the present work, sunflower hybrids were evaluated in terms of their response to inoculation with P. helianthi isolates from two different sites of Argentina: Pergamino (PERG) and Paraná (PAR). Stem canker length and proportion of broken stems were the investigated response variables. Differences in stem canker length were detected among hybrids. Fungus isolate from PERG produced longer stem cankers and higher number of broken stems than the one from PAR. From all the hybrids tested, Dekasol 3881 was the one with the lowest harm effects when exposed to the most pathogenic fungus isolate. Considering its low stem breaking effect, the isolate from Paraná would be more appropriate for breeding programmes, allowing plants selected for short canker length to remain standing for their use in the improvement of sunflower populations by crossing.